2021
DOI: 10.1101/2021.01.31.428746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AMycobacterium tuberculosiseffector targets mitochondrion, controls energy metabolism and limits cytochrome c exit

Abstract: Host metabolism reprogramming is a key feature of Mycobacterium tuberculosis (Mtb) infection that enables the survival of this pathogen within phagocytic cells and modulates the immune response facilitating the spread of the tuberculosis disease. Here, we demonstrate that a previously uncharacterized secreted protein from Mtb, Rv1813c manipulates the host metabolism by targeting mitochondria. When expressed in eukaryotic cells, the protein is delivered to the mitochondrial intermembrane space and enhances host… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The Rv1269c gene encodes a secreted protein with an unknown function. It was shown that Rv1269c product may damage the host’s mitochondria [ 33 ]. Based on a proteomic approach, the study [ 34 ] claimed that Rv1269c is more efficiently secreted in modern Beijing isolates because it was significantly more abundant in cell lysates of ancient Beijing isolates, whereas the transcriptional levels were similar for modern and ancient Beijing MTB.…”
Section: Discussionmentioning
confidence: 99%
“…The Rv1269c gene encodes a secreted protein with an unknown function. It was shown that Rv1269c product may damage the host’s mitochondria [ 33 ]. Based on a proteomic approach, the study [ 34 ] claimed that Rv1269c is more efficiently secreted in modern Beijing isolates because it was significantly more abundant in cell lysates of ancient Beijing isolates, whereas the transcriptional levels were similar for modern and ancient Beijing MTB.…”
Section: Discussionmentioning
confidence: 99%
“…Upon expression in eukaryotic cells, it is transported to the intermembrane space of mitochondria, thereby boosting ATP production through the enhancement of the oxidative phosphorylation metabolic pathway. This, in turn, influences the metabolic and apoptotic responses in macrophages infected with Mtb ( Martin et al., 2023 ). As a conserved latency antigen, Rv1813c represents a promising candidate for vaccine development.…”
Section: Antigen Selection For Tb Vaccinesmentioning
confidence: 99%